2013
DOI: 10.1016/j.jacc.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Nature of Unfunded Published Cardiovascular Research

Abstract: Considerable published cardiovascular research is currently being conducted without direct financial support. This is particularly true for young clinical investigators. The inability to accommodate this investigation in the medical enterprise might substantially diminish the amount of new knowledge coming forth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the context where the literature also suggests that early career academics may have less funding success, at least in the sciences (Mai et al 2013), there was a fair range of career stages represented: senior, mid-and early career (see Table 1). Career-stage can be a fluid understanding though; I felt that some of those who referred to themselves as mid-career could be regarded as senior in the position that they held, and as one lecturer remarked: 'I worked for 20 years outside academia before entering and I found myself being identified as somebody in the early stages of their career'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context where the literature also suggests that early career academics may have less funding success, at least in the sciences (Mai et al 2013), there was a fair range of career stages represented: senior, mid-and early career (see Table 1). Career-stage can be a fluid understanding though; I felt that some of those who referred to themselves as mid-career could be regarded as senior in the position that they held, and as one lecturer remarked: 'I worked for 20 years outside academia before entering and I found myself being identified as somebody in the early stages of their career'.…”
Section: Methodsmentioning
confidence: 99%
“…Others have carried out analyses of funding acknowledgements for academic journal articles 1 and/or surveyed article authors, usually USA science/medical-based, and found a good proportion of these are based on unfunded research. Examples range from 23 to 84 per cent depending on the discipline concerned and the methodology used in the analysis Moore 1993, 1995;Stein, Rubenstein, and Wachtel 1993;Mai et al 2013). There are indications that unfunded research may hidden away in funded grant time (Stein, Rubenstein, and Wachtel 1993), or undertaken at evenings and at weekends, with particular detriment to women, and perhaps with institutional tacit approval (Barrett and Barrett 2011;Kernohan 2015;Mai et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, a considerable number of highquality studies in cardiovascular research are conducted without direct financial support, especially by young clinical investigators. 23 The present study has some limitations and strengths. First, we analyzed the corresponding author country of origin as a proxy of native language.…”
mentioning
confidence: 89%